2020
DOI: 10.1039/d0cc00382d
|View full text |Cite
|
Sign up to set email alerts
|

A new FRET probe for ratiometric fluorescence detecting mitochondria-localized drug activation and imaging endogenous hydroxyl radicals in zebrafish

Abstract: A new FRET probe has been prepared and successfully used for imaging hydroxyl radicals generated by drug activation and endogenous hydroxyl radicals in zebrafish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Indeed, in the reported • OH probes containing amide groups, the amide was not the reaction site. 29,44 Moreover, singlet oxygen ( 1 O 2 ) will not interfere with the response of probe FDOCl-22 toward HOCl (Figures S12 and S13). These results indicated that the probes had good selectivity for HOCl.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the reported • OH probes containing amide groups, the amide was not the reaction site. 29,44 Moreover, singlet oxygen ( 1 O 2 ) will not interfere with the response of probe FDOCl-22 toward HOCl (Figures S12 and S13). These results indicated that the probes had good selectivity for HOCl.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the present work, the insensitivity of FDOCl-21 (5 μM) and FDOCl-22 toward • OH may be because the experimental conditions that mimic the normal physiological conditions do not meet the requirements of harsh condition for the reaction between • OH and amide. Indeed, in the reported • OH probes containing amide groups, the amide was not the reaction site. , Moreover, singlet oxygen ( 1 O 2 ) will not interfere with the response of probe FDOCl-22 toward HOCl (Figures S12 and S13). These results indicated that the probes had good selectivity for HOCl.…”
Section: Resultsmentioning
confidence: 99%
“…So far, FRET fluorescent probes have been widely reported in recent years (16)(17)(18)(19)(20). FRET fluorescent probes not only have mature applications in the detection of metal ions (21), ROS (22) and RNS (23), but also can be used to sense biological macromolecules (e.g., proteins (24)(25)(26)(27), nucleic acids (28,29)), and even be used for the visualization of changes in the cell microenvironment and the monitoring of pathophysiological processes (30)(31)(32)(33)(34). There is no doubt that FRET probes are of great significance to biological research.…”
Section: Introductionmentioning
confidence: 99%
“…Model organisms ranging from invertebrates, such as Caenorhabditis elegans (Beam et al 2012 ) and Drosophila melanogaster (Wang et al 2004 ), to vertebrates like Xenopus laevis and the zebrafish Danio rerio have all been studied with FCS (Shi et al 2009a , b ). The zebrafish, in particular, has greatly furthered the field of developmental biology with the use of FCS and other confocal-microscopy-related quantification technologies such as FCCS, Förster resonance energy transfer (FRET) and fluorescence recovery after photobleaching (FRAP) (Deng et al 2020 ; Wang et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%